On generic structures preserving elementary equivalence and elementary embeddability - Sudoplatov, S.V. (KSU Publ., 2018)
We consider criteria for elementary equivalence and elementary embeddability for generic structures. They use classical characterizations for the general case. The criterion for elementary equivalence is based on the well known Fra¨ıss´e–Taimanov–Ehrenfeucht overturning method. The criterion for elementary embeddability uses the known Tarski–Vaught test.
Элементарлық енгiзiлудi және элементарлық эквиваленттiлiктi сақтайтын генерикалық құрылымдар туралы
О генерических структурах, сохраняющих элементарную эквивалентность и элементарную вложимость
Keywords: generic structure; elementary equivalence; Fra¨ıss´e–Taimanov–Ehrenfeucht’s method; elementary embeddability; Tarski-Vaught test